ANALYSIS OF FACTORS CAUSING OPERATIONAL FAILURE OF LOGISTICS COMPANIES IN THE E-COMMERCE ERA: A CASE STUDY OF JET EXPRESS - Asep Dony Suhendra; Ayu Azizah; Eni Reptiningsih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Jet Express is a shipping service company in Indonesia that once grew rapidly along with the rise of the e-commerce trend. However, in recent years, the company has faced a crisis characterized by declining service, a reduction in operational branches, and declining customer trust. This study aims to analyze the factors causing the Jet Express crisis, its impact on the logistics industry, and potential recovery strategies. The study used a descriptive qualitative approach through literature review and secondary data analysis. The results indicate that the Jet Express crisis was influenced by weak management, intense competition, and a failure to adapt to service digitalization.